Estrogen receptor-alpha gene XbaI A > G polymorphism influences short-term cognitive decline in healthy oldest-old individuals - Amanda Caroline Silva Chaves (2022)
This prospective study aimed to evaluate the influence of the -351A/G XbaI polymorphism in the estrogen receptor-alpha (ESR-1) gene on global cognitive scores of a community sample of healthy oldest-old individuals within one year of follow up. Methods The individuals were categorized in two groups according to the presence or absence of cognitive decline. Cognitive data were related to genetic information. Results The XbaI -351 AA genotype was more common among cognitive decliners, while -351G allele carriers showed cognitive stability or improvement. Conclusion These results suggest that ESR-1 could be associated with one-year cognitive decline in healthy oldest-old individuals, since the estrogen pathway may be involved with neuroprotection, even in healthy brain aging.